Peran Identifikasi Merek dan Citra Merek dalam Mempengaruhi Cinta kepada Merek - Hendrasto, Ferdian (Jurnal Ekonomi Modernisasi, 2017)
This research aims to synthesize two major antacedents of brand love, which are brand identification and brand image. Research is conducted using multiple regression analysis, whereas data collection is conducted using online questionnaire. The sample of this research is community members of a prominent video games franchise, The Elder Scrolls series. The empirical result shows that both variables not only influence brand love partially, but also simultaneously. Thus, practitioners who aim to improve the consumer-brand relationship should develop their marketing strategy around a strong brand image and a solid brand identification.